Experimental and numerical research of crack propagation process and energy dissipation law of grouting specimens under radial impact load - Zhu, Chang-Xing; Sun, Jia-Xin; Gong, Jian; Wang, Feng-E (Frontiers in Earth Science, 2023)
Five air pressures are used to conduct an impact test based on the split Hopkinson pressure bar (SHPB) test system to study the crack evolution process and energy dissipation law of the cemented rock under impact load, and a high-speed camera captures the crack expansion process. The failure mechanism of the specimens is analyzed from the perspective of dynamic failure process and energy dissipation, and the relationship between crack evolution process and energy dissipation are discussed under five strain rates. The spatial distribution of the specimen components visualized by the image reconstruction technology and the LS-DYNA mesoscopic model is established. The crack evolution process and failure mode of the specimens are well simulated compared with the indoor and simulation tests. Results show that the proportion of dissipated energy increases with the increase in strain rate, and the dynamic tensile strength and peak strain of the specimens increase. It has an obvious strain rate effect. The crack evolution process of the model is quantitatively described under an impact load, which is divided into four stages, namely, no crack stage, crack slow development stage, crack accelerated propagation stage, and crack penetration stage. The crack evolution process and failure modes are consistent under different strain rates compared with the indoor and simulation test result. When the specimens are destroyed, the energy dissipation rate fluctuates from 10% to 13%. The dissipated energy of cement paste accounts for more than 90% of the total dissipated energy. The cement paste degrades first and most severely affected. The strength of the cement paste has a great influence on the strength of grouting-reinforced rock mass. This study provides a reference to evaluate the cemented rock under a dynamic load.